Development of Heat-Stable Cookie Filling : Effect of Emulsifiers on Fat Crystallization - Kirkopoulou,Eirini; Arab,Fatemeh (2025)
Emulsifiers can influence fat crystallization through multiple mechanisms: by promoting or in-hibiting nucleation, modifying polymorphic transitions, or enhancing oil-binding capacity. In collaboration with Palsgaard A/S, this thesis aimed to evaluate the functional impact of selected emulsifiers from their portfolio on the thermal and textural stability of fat-based biscuit cream fillings. The goal was to develop a heat-stable formulation capable of withstanding elevated storage and transport temperatures. Six oil blends were initially screened based on their solid fat content (SFC), texture and feasibil-ity, resulting in the selection of an optimal fat matrix. This base was then modified with five different emulsifiers, applied at three concentrations, to investigate their influence on fat crystal-lization behaviour and cream performance. A variety of analytical techniques, including Nuclear Magnetic Resonance (NMR), Differential Scanning Calorimetry (DSC), rheological analysis, texture analysis along with shelf-life observation was employed to characterize the structural and functional properties of the formulations. The results demonstrated that both emulsifier composition and concentration significantly influ-enced cream firmness, oil retention and spreadability. Crystallizers rich in triglycerides (such as Palsgaard® CrystalPromoter 6117 and Palsgaard® OilBinder /CrystalPromoter 6121) promoted robust crystal network formation and enhanced thermal stability. In contrast, emulsifiers with higher levels of mono- and diglycerides (e.g., Palsgaard® DMG 0091 and Palsgaard® DMG 0298) yielded softer textures but exhibited reduced oil-binding capacity. Overall, Palsgaard® CrystalPromoter 6191 at 0.5% demonstrated the most balanced perfor-mance across key parameters, combining structural integrity, spreadability and oil retention. This supports the conclusion that intermediate concentrations of effective crystallizers offer a promis-ing approach for developing heat-resistant, consumer-acceptable cream fillings.
Keywords: Emulsifiers; Cream fillings; Fat-based fillings; Crystallizers; Fat crystallization; Triacylglycerols; Food Engineering Nutrition and Food Chemistry